INITIATION OF BUMDES TOURISM VILLAGE AS A MEANS OF EQUALIZATION IN COMMUNITY LIVELIHOODS IN THE DISTRICT OF KARIMUNJAWA - Kiswanto, Kiswanto; Jati, Kuat Waluyo; Kristi, Nuke Monika (Universitas Negeri Semarang, 2019)
Communities in Karimunjawa Subdistrict have problems related to income inequality, most of the people there as farm laborers even though Karimunjawa is a well-known tourism area in Indonesia. This happens because the surrounding community has not been fully involved to play an active role in tourism development. The purpose of this community service activity is to increase public awareness in Karimunjawa Subdistrict on the potential of the village to be willing to develop themselves to manage and develop companion and complementary businesses as a tourist village so that livelihoods can shift from farm labor to the production of tourism products. The next goal is the initiation of the establishment of a village-owned enterprise (BUMDes) which will manage the village tourism activities. The method of implementing community service activities is through lectures, questions and answers, discussions, simulations, and assistance. The strategic steps used in this activity are (1) providing insight into the concept of tourism villages and the importance of BUMDes in improving welfare , (2) providing knowledge about the potential use of villages for tourism objects through management through BUMDes , (3) discussion and question and answer by providing opportunity to the community and village apparatus , (4) provide an overview and simulation of the initiation of the establishment of BUMDes , (5) assistance to the community and village apparatuses to prepare a village tour and initiation of the establishment of BUMDes , and (6) evaluation of the results of community service activities that have been carried out . The dedication that has been done has been able to provide views for village managers on how to do good governance. During the question and answer session, what became the focal point of the village manager was the program that had been running in relation to tourism in the village. Tourism has been running for a number of years, but has not given maximum results according to residents, even though the funds poured out are already quite a lot and other fields need to be considered as well. The results of the service that has been done are greatly appreciated by the village officials. Provision of knowledge of village officials about knowledge related to various rules that must be obeyed. Masyarakat di Kecamatan Karimunjawa memiliki permasalahan terkait dengan ketimpangan mata pencaharian, masyarakat di sana sebagian besar sebagai buruh tani padahal Karimunjawa merupakan daerah pariwisata yang terkenal di Indonesia. Hal ini terjadi karena masyarakat sekitar belum diikutsertakan secara penuh untuk berperan aktif dalam pengembangan pariwisata. Tujuan kegiatan pengabdian ini adalah untuk meningkatkan kesadaran masyarakat di Kecamatan Karimunjawa atas potensi desa yang dimiliki agar bersedia mengembangkan diri untuk mengelola dan mengembangkan usaha pendamping dan pelengkap sebagai desa wisata sehingga mata pencaharian dapat beralih dari buruh tani menjadi produksi produk-produk wisata. Tujuan berikutnya adalah inisiasi berdirinya sebuah badan usaha milik desa (BUMDes) yang akan mengelola kegiatan desa wisata. Metode pelaksanaan kegiatan pengabdian kepada masyarakat adalah dengan ceramah, tanya jawab, diskusi, simulasi, dan pendampingan. Langkah strategis yang digunakan dalam kegiatan ini adalah (1) memberi wawasan tentang konsep desa wisata dan pentingnya BUMDes dalam meningkatkan kesejahteraan, (2) memberi pengetahuan tentang pemanfaatan potensi desa untuk objek wisata dengan pengelolaan melalui BUMDes, (3) diskusi dan tanya jawab dengan memberikan kesempatan kepada masyarakat dan perangkat desa, (4) memberikan gambaran dan simulasi tentang inisiasi pendirian BUMDes, (5) pendampingan kepada masyarakat dan perangkat desa menyiapkan desa wisata dan inisiasi pendirian BUMDes, dan (6) evaluasi hasil dari kegiatan pengabdian yang telah dilakukan. Pengabdian yang telah dilakukan telah mampu memberikan pandangan bagi pengelola desa untuk bagaimana melakukan tata kelola yang baik. Pada saat sesi tanya jawab, hal yang menjadi titik fokus pengelola desa adalah tentang program yang telah berjalan terkait dengan wisata yang ada di desa tersebut. Pariwisata sudah dijalankan beberapa tahun, namun belum memberikan hasil yang maksimal menurut warga, padahal dana yang digelontorkan sudah cukup banyak dan bidang lain butuh untuk diperhatikan juga. Hasil dari pengabdian yang telah dilakukan sangat diapresiasi oleh para perangkat desa. Pembekalan pengetahuan perangkat desa tentang pengetahuan terkait dengan berbagai aturan yang harus dipatuhi.